Pengembangan Model Manajemen Pendidikan Holistik Berbasis Nilai Keislaman di Madrasah Ibtidaiyah - Haris Sandi Yudha; Asep Supriatna; Ahmad Riyadi; Candra Mochamad Surya; Sony Kuswandi (CV. Creative Tugu Pena, 2025)
Education based on Islamic values ​​has an important role in shaping students' character based on religious principles. This research aims to analyze the implementation of educational management based on Islamic values ​​and its influence on the formation of student character at Madrasah Ibtidaiyah Tarbiyatul Athfal. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with school principals, teachers and students as well as observations of school activities, which were then analyzed thematically. The research results show that the implementation of educational management based on Islamic values ​​at Madrasah Ibtidaiyah Tarbiyatul Athfal plays a significant role in forming student character. Learning that integrates Islamic values ​​such as honesty, discipline and responsibility has succeeded in encouraging students to be more active and responsible in teaching and learning activities and in everyday life. Religious programs, such as congregational prayers and Islamic studies, are an important part of supporting student character formation. The implication of this research is the need for an educational management model based on Islamic values ​​to support the formation of better student character. In this way, madrasas can create an environment that supports not only academic development, but also strong moral character.